Application of Innovative Technologies in Teaching Scientific and Pedagogical Heritage of Thinkers of the East - Alimkhanova Nigorakhon Amilevna (International Journal on Integrated Education, 2022)
Oriental scholars and thinkers have put forward unique ideas for the upbringing and career guidance of the younger generation. Careful study, analysis, systematization of scientific heritage and comparison with the achievements of world science in this field expands the opportunities for self-understanding and further enhances the prestige of our people in the world community. The study of the history of our national pedagogy, especially the experience of our ancestors over the centuries in educating the younger generation, will undoubtedly serve to improve the educational process. the article analyses special features of using innovative technologies in teaching process. In this article we defined issues based on application of innovative technologies in teaching scientific and pedagogical heritage of thinkers of the east.